Immediate Reversal of Dabigatran by Idarucizumab Prior to Laboratory and Imaging Results in Acute Stroke - Hieber, Maren; Bardutzky, Juergen (Frontiers in Neurology, 2019)
We report a case of intravenous thrombolysis in acute ischemic stroke of anterior choroidal artery following the antagonization of dabigatran with idarucizumab. The recent approval of idarucizumab enables intravenous thrombolysis despite preexisiting oral anticoagulation with dabigatran, but raises the question of the optimal management and work flow of patients under medication with dabigatran and with acute neurological deficit, highly suspicious for an acute cerebrovascular event. In contrast to hitherto case reports and series, here, we explicitly refrained from awaiting the results of the thrombin time, as a marker for present anticoagulation by dabigatran, as well as the results of cerebral imaging before administration of idarucizumab. Based on the presented case we propose this approach to minimize door-to-needle time of intravenous thrombolysis in acute ischemic stroke and thus to enhance the chance for a good outcome.